(untitled) (Asian Journal of Medical and Biological Research, 2020)
Climate change is a very common phenomenon which may affect rural livelihoods. A sustainable rural livelihoods approach was taken for this study to observe household incomes and any impact of climate to the livelihoods. It was found that there was negative correlation (Pearson value -0.449) to the income of males and females in 2014. Assumption of impact of climate change on income was not statistically significant in male farmers while it was statistically significant (Pearson value 0.332) in the year 2013 for female respondents. This current study suggests diversification in income generating activities and introduction of fair trade for betterment of the fishers Asian J. Med. Biol. Res. September 2020, 6(3): 418-424